Analisis Sistem Tanggap Darurat Kebakaran di Lapangan Penumpukan Terminal Petikemas PT. Nilam Port Terminal Indonesia Tanjung Perak Surabaya - Husna, Imroatul; Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2020)
PT. Nilam Port Terminal Indonesia is a multipurpose port that provides container loading and unloading terminal operator services at the port. A fire in a container terminal can cause a lot of losses because it affects the value of assets, work processes and high job opportunities. One of the efforts to reduce the risk and impact of fires is the existence of an emergency response system. One of the efforts to reduce the risk and impact caused by fire requires the application of a good and correct emergency response system in accordance with applicable regulations. The purpose of this study is to analyze the application of an emergency response system in an effort to prevent and control fire disasters at the container terminal of PT. Nilam Port Terminal Indonesia. This research is a descriptive qualitative research, and uses primary data sources obtained from sources and secondary data obtained from documents containing descriptive facts through interviews and field observations. This research was conducted directly at PT. Nilam Port Terminal Indonesia. In this research, we will describe how the implementation of the fire emergency response system in PT. Nilam Port Terminal Indonesia. The results of this analysis can be concluded that PT. Nilam Port Terminal Indonesia has implemented a fire emergency response system in accordance with applicable regulations, but there are several implementations that are not yet optimal, such as improper placement and maintenance of fire extinguishers, workers' awareness of fire hazards, and less fire emergency response training.